ChemInform Abstract: Multicomponent Cascade Synthesis of Trifluoroethyl Isoquinolines from Alkynes and Vinyl Azides. Issue 20 (April 2016) - Liu, Kai; Chen, Shuang; Li, Xing Guang; Liu, Pei Nian
Abstract: This novel approach, combining traditional Rh‐catalyzed C—H activation and Tognis reagent, provides a direct, concise access to trifluoroethylisoquinolines in moderate to good yields with good chemoselectivity and is appropriate to construct complex trifluoromethylated compounds in a single operation.